2015
DOI: 10.3389/fpsyg.2015.00476
|View full text |Cite
|
Sign up to set email alerts
|

The development of ingroup favoritism in repeated social dilemmas

Abstract: In two comprehensive and fully incentivized studies, we investigate the development of ingroup favoritism as one of two aspects of parochial altruism in repeated social dilemmas. Specifically, we test whether ingroup favoritism is a fixed phenomenon that can be observed from the very beginning and remains stable over time, or whether it develops (increases vs. decreases) during repeated contact. Ingroup favoritism is assessed through cooperation behavior in a repeated continuous prisoner's dilemma where partic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 42 publications
2
17
0
1
Order By: Relevance
“…Social cooperation, its evolution and stability can be understood from a number of perspectives: social value orientation (see Balliet et al, 2009); social norms (e.g., Buckholtz and Marois, 2012;Fehr and Fischbacher, 2004); group bias (e.g., Dorrough et al, 2015;McAuliffe and Dunham, 2016); conditional cooperation or reciprocity (e.g., Kocher et al, 2008;Fischbacher and Gaechter, 2010;Smith, 2013); context-specificity (e.g., Rand and Nowak, 2013); and so on.…”
Section: Introductionmentioning
confidence: 99%
“…Social cooperation, its evolution and stability can be understood from a number of perspectives: social value orientation (see Balliet et al, 2009); social norms (e.g., Buckholtz and Marois, 2012;Fehr and Fischbacher, 2004); group bias (e.g., Dorrough et al, 2015;McAuliffe and Dunham, 2016); conditional cooperation or reciprocity (e.g., Kocher et al, 2008;Fischbacher and Gaechter, 2010;Smith, 2013); context-specificity (e.g., Rand and Nowak, 2013); and so on.…”
Section: Introductionmentioning
confidence: 99%
“…Outgroup aggression in earlier rounds promoted altruistic giving in later rounds in comparison with the experimental condition that did not allow aggression. Dorrough, Glöckner, Hellmann and Ebert [37] asked members of two real world groups to play a sequence of 20 simultaneous PD games, first with 10 different members one group (ingroup or outgroup, counterbalanced), then with 10 different members of the other group. They found no evidence of ingroup favoritism at round 1, but found that ingroup favoritism increased over repeated contacts, and was linked to the expectation of ingroup reciprocation, especially in the shift between groups between rounds 10 and 11.…”
Section: Introductionmentioning
confidence: 99%
“…Chen and Li [30], Cacault et al [36], and Dorrough et al, [37] studied ingroup favoritism over a sequence of rounds, and showed that subsequent behaviors may be influenced by prior actions. Nonetheless, these experiments lacked the responsive quality of true interaction.…”
Section: Introductionmentioning
confidence: 99%
“…Hence this human nature is also responsible for creating differences. 39,[45][46][47] This human tendency has helped them in evolution in early phases but in later phases of evolution, human wisdom helped them to perform better than animals. Most of our behavior depends on our DNA and human DNA resembles to that of animals especially chimpanzee, to a very large extent.…”
Section: Superioritymentioning
confidence: 99%